Philantrophy in Education of Religious Tolerance in Kurikulum Merdeka at Elementary School Temanggung District - Utomo, Sigit Tri; Ridwan, Muhammad; Amirudin, Yoyok; Nida, Dzikrina Khoirun; Yusuf, Ahmad; Tamama, Muna Badru (Analisa: Journal of Social Science and Religion, 2023)
The multicultural Indonesian nation consisting of various tribes, languages, ethnicities, cultures, and religions must uphold tolerance education. including the implementation of the "Kurikulum Merdeka" in educational units in schools. Various cases of religious intolerance show a lack of voluntary action through an understanding of the treatment of volunteerism for social purposes through love (philanthropy) in the form of acts of generosity (compassion). This paper discusses the Philanthropy of Religious Tolerance Education in the Implementation of the "Kurikulum Merdeka" at Al-Kautsar Elementary School and Pangudi Utami Elementary School.This research qualitative field research with a data collection approach through observation, interviews, and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion. The results of the study show that philanthropy is always closely related to things that are engaged in charity or are closely related to material elements. This narrow view is currently beginning to erode, especially with the increasing interest of school students in philanthropic activities which are closely related to the behavior of those who do them out of concern. The meaning of philanthropy is expanding and developing. Philanthropic activities are increasingly organized and directed. During modern currents, forms of philanthropy emerge in society, one of which is philanthropy in implementing “Kurikulum Merdeka” with two different schools with students from Pangudi Utami Catholic Elementary School and Al Kautsar Islamic Elementary School.